PENGGUNAAN MEDIA PASHIBI (PAPAN SEJARAH HINDU BUDHA ISLAM) PADA MATA PELAJARAN IPAS KELAS 4 PADA HASIL BELAJAR SISWA - Alifandi Hafidz Nur Ihsan; Zuni Eka Tiyas Rifayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the use of PASHIBI media (Hindu–Buddhist–Islamic History Board) and its effect on students’ learning outcomes in the Natural and Social Sciences (IPAS) subject for fourth-grade students at UPT SD Negeri 93 Gresik. This research employed a qualitative approach with a case study design. The research subjects consisted of one fourth-grade teacher and 13 fourth-grade students. Data were collected through observation, in-depth interviews, and documentation of students’ learning outcomes. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with source triangulation used to ensure data validity. The results showed that the use of PASHIBI media increased students’ activeness, motivation, and understanding of Hindu–Buddhist–Islamic history material. PASHIBI media helped students understand historical concepts more concretely through attractive visual displays, making it easier for students to remember the names of kingdoms, figures, and historical heritage. In addition, the learning atmosphere became more interactive and enjoyable, which had a positive impact on improving students’ learning outcomes. Based on these findings, it can be concluded that PASHIBI media is effective as a learning medium for fourth-grade IPAS subjects and can serve as an innovative alternative medium to improve elementary school students’ learning outcomes.